The Poet, the Practitioner, and the Beholder: Remarks on Philip Hefner's “Created Co-Creator” - Westhelle, Vitor (Zygon, 2004)
Philip Hefner's notion of the created co-creator is treated here as a concept in its procedural sense. The concept as a theoretical construct offers a substantial account of human capabilities, their ingenuity to transcend the intrinsic and bring about a new order of growth and development. However, the limitation of this concept is its neatness. It suppresses that which cannot be suppressed. This otherwise straightforward concept fails to give a realistic description of the human in situations of being on the edge that points to an end where there are no alternatives or negotiations. What is promising in the created co-creator is that it is able to incorporate elements of the Western philosophical and theological anthropology. I propose that the created co-creator reflects and elaborates the Aristotelian human attributes of theoria, praxis, and poiesis.